Risk, courage, and women : contemporary voices in prose and poetry - Waldron, Karen A., 1945-; Labatt, Laura M., 1943-; Brazil, Janice H., 1951- (Book collections on Project MUSE., 2007)
A collection of narratives, essays, and poems that includes an interview with Maya Angelou and pieces by Naomi Shihab Nye, Pat Mora, Rosemary Catacalos, and many others. Each work relates how women have demonstrated courage by taking a risk that has changed their lives.